Low Testosteron Level in Worsening Symptom of Heart Failure Patients: A Literature Review - Ardiansyah, Ryan; Sauqy, Akhmad Sandy (Universitas Airlangga, 2025)
Abstract Background: Heart failure can be caused by a variety of factors, including high blood pressure, coronary artery disease, diabetes, obesity, smoking, and genetics. Testosterone is the primary male hormone responsible for regulating sex differentiation, producing male sex characteristics, spermatogenesis, and fertility. It plays a crucial role in various bodily functions, including the development of male reproductive tissues and the maintenance of muscle mass and bone density. Testosterone levels have been found to be significantly decreased in heart failure patients compared to healthy controls. This suggests that low testosterone levels may play a role in the development or progression of heart failure. The relationship between testosterone and heart failure is complex and warrants further investigation. Additional research is needed to better understand the role of testosterone in heart failure and to determine the optimal therapeutic strategy for its management. Based on these data, we decided to further investigate how low testosterone levels affect the symptoms of heart failure patients. Aims: This literature review study aims to examine further how low testosterone levels affect the symptoms of heart failure patients. Method: Journals in this literature review used three databases, including Google Scholar, PubMed, and Science Direct, using the keywords